Utilização da área livre de pavimentação nas calçadas para ornamentação visando benefícios ambientais - Emer, Aquélis Armiliato (2014)
The global trend of people concentration in urban areas, allied with the lack of planning of cities has caused serious environmental damage that are reflected in the quality of life of the population. The waterproofing excessive of soil and lack of vegetation in cities are some of the main consequences of urbanization that can cause flooding of streets and formation of environment little aesthetic and attractive for social life. In this context, the objective this work was to evaluate the feasibility of installation of ornamental plants in the free areas of the sidewalks in the city of Pato Branco, PR. The experiment was conducted in the urban area of Pato Branco city, PR in an area composed by exposed soil and sidewalk. Were planted seedlings of ornamental: Kalanchoe blossfeldiana (Kalanchoe), Acalypha reptans (Copperleaf), Tradescantia pallida var. purpurea (Purple Queen), Chlorophytum comosum (Spider plant) and Ophiopogon japonicus (Mondo grass). Were evaluated the characteristics of the soil, plant development and environmental perception of residents, passers-by and non residents of the place where the experiment was implemented. The soil had no significant changes in morphological classification in relation to this under native vegetation near the site, even if observed changes in particle size and chemical composition of the soil. Iit was found increased levels of all chemical elements, especially of micronutrients. For all the evaluated species the development in urban areas was satisfactory and that, the Purple Quenn and Copperleaf were the species that showed best performance for mulching and Speider plant was the one that had the greatest effect on the rate of infiltration. In the perception of most interviewees seem to recognize the importance of vegetation in cities and relates soil permeability with the preservation of the environment and water infiltration. Most respondents enjoy herbaceous vegetation, has preference for species with flowers and relates the presence f this type of plant with embellishment the streets. The psychological wellbeing was among the most important functions performed by herbaceous species within the cities for all interviewed. Most respondents proved receptive to the use of the ornamental species on sidewalks and showed preference for Kalanchoe. The main advantage viewed by respondents was the enviroment more beautiful and the main drawback to greater need for maintenance and greater dirt. Most respondents would adopt on their own this type of strategy and would help mainly with the maintenance of the plants. Considering all the results it can be inferred that, the Speider plant was concentrated species that as much desirable attributes and that the use of ornamental plants in the free areas of paving on sidewalks is an effective strategy on the technical point of view and is well accepted by the population.